Ethical Considerations in Advanced Data Analytics : Balancing Innovation and Privacy - Lokeshkumar Madabathula (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The evolving landscape of data analytics presents organizations with dual challenges of maximizing innovation while maintaining ethical responsibilities. This article explores the complex relationship between technological advancement and ethical data management, examining key areas including privacy preservation, algorithmic fairness, and regulatory compliance. Through analysis of real-world implementations across healthcare, urban planning, and enterprise sectors, the article presents evidence-based frameworks for ethical data governance. The article highlights the critical role of data professionals in developing and maintaining ethical guidelines, emphasizing the importance of technical leadership and public engagement. Additionally, the article examines emerging challenges in data ethics, providing insights into future considerations for organizations navigating the intersection of innovation and privacy in data analytics.